NanoSQUIDs based on Nb nanobridges. (June 2020) - Rodrigo, R.; Faley, M.I.; Dunin-Borkowski, R.E.
Abstract: We have developed nanoSQUIDs with Josephson junctions in the form of Nb nanobridges, whose thickness, width and length are in the order of the superconducting coherence length in Nb thin films, which is 15 nm at 4.2 K in 20-nm-thick films. The thin Nb films were deposited using pulsed DC magnetron sputtering. A 30-nm-thick mask of PMMA resist was formed by electron beam exposure using a dose of 50 mC/cm 2 at 100 kV, at which PMMA operates as a high-resolution negative resist. Compared to the previously used HSQ resist, PMMA has a much better availability, lower health risk, a longer shelf life and a simpler development procedure, while maintaining sufficient resolution. Both Nb nanobridges with widths down to 10 nm and nanoSQUIDs with the incorporated nanobridges were fabricated using reactive ion etching with pure SF6 gas. They show non-hysteretic I(V) -characteristics and a modulation of the critical current at both directly injected or externally applied magnetic field fluxes. The obtained spin sensitivity of S n 1 / 2 ≅ 135 μ B / √ H z is very promising for the use of the nanoSQUIDs as magnetic field sensors for the investigation of nanoscale objects.